Adult capped dental payment model applied within a university setting: an Australian reflective case study - Jennifer Hanthorn Conquest; John Skinner; Estie Kruger; Marc Tennant (BMC, 2021)
Abstract Background Capitation models of care in dentistry started around 1973 with varying degrees of success in meeting the needs of the individuals and expectations of the participating private practitioners. These studies mostly identified that capitation payments resulted in under treatment whilst fee-for-service models often led to over treatment. The objective of this study was to develop a new way of doing business using an outsourcing capitation model of care to meet population health needs and activity-based funding requirements of rural Local Health Districts with a local university dental school. This payment model is an alternate referral pathway for public oral health practitioners from the existing New South Wales Oral Health Fee-for-Service Scheme that focuses on urgent treatment to one that offers an all-inclusive preventive approach that concentrates on sustaining good long-term oral health for the individual. Method The reflective study analysed various adult age cohorts (18-24, 25-34, 35-44, 45-54, 55-64, 65-74 and 75 + years) based on 950 participants randomly selected from the Greater Southern adult public dental waiting lists. The study's capitation formula was derived from NSW government adult treatment items (n = 447,625). Dental care was provided through the local university's dental clinics utilising only dental students under clinical supervision. All data were sourced from NSW Oral Health Data Warehouse during 1 January 2012-30 June 2018 and analysed by using SAS 9.3 and Version 13 Microsoft Excel. Results There were 10,305 dental care items and 1129 capitation courses of care totalling A$599,026. This resulted in an average of 11 dental care items being provided to each participant. The capitation payment formula utilising the most provided dental care items of 100 individual patients proved to be economical and preventive focused. Conclusion The systematic reflection showed that this unique methodology in developing an adult capitation payment formula associated to diagnostic pathways that resulted in: (i) more efficient usage of government expenditure on public dental services, (ii) provision of person-centred courses of dental care, and (iii) utilisation of university dental education programs to best practice treatment and holistic care.